Mesoangioblasts at 20: From the embryonic aorta to the patient bed - Cossu, Giulio; Tonlorenzi, Rossana; Brunelli, Silvia; Sampaolesi, Maurilio; Messina, Graziella; Azzoni, Emanuele; Benedetti, Sara; Biressi, Stefano; Bonfanti, Chiara; Bragg, Laricia; Camps, Jordi; Cappellari, Ornella; et al. (Frontiers in Genetics, 2023)
In 2002 we published an article describing a population of vessel-associated progenitors that we termed mesoangioblasts (MABs). During the previous decade evidence had accumulated that during muscle development and regeneration things may be more complex than a simple sequence of binary choices (e.g., dorsal vs ventral somite). LacZ expressing fibroblasts could fuse with unlabelled myoblasts but not among themselves or with other cell types. Bone marrow derived, circulating progenitors were able to participate to muscle regeneration, though in very small percentage. Searching for the embryonic origin of these progenitors, we identified them as originating at least in part from the embryonic aorta and, at later stages, from the microvasculature of skeletal muscle. While continuing to investigate origin and fate of MABs, the fact that they could be expanded in vitro (also from human muscle) and cross the vessel wall, suggested a protocol for the cell therapy of muscular dystrophies. We tested this protocol in mice and dogs before proceeding to the first clinical trial on Duchenne Muscular Dystrophy patients that showed safety but minimal efficacy. In the last years, we have worked to overcome the problem of low engraftment and tried to understand their role as auxiliary myogenic progenitors during development and regeneration.